PENGARUH MODIFIKASI ALAT REBOUNDER TERHADAP KETERAMPILAN PASSING PADA ATLET SEPAK BOLA GELORA FC SINTANG U15 - Ari Rahmana; Andika Triansyah; Mimi Haetami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to improve the basic technical skills of passing by modifying the rebounder on the Gelora Fc Sintang U15 soccer athletes. This study uses quantitative analysis with experimental research methods, and test as the instrument of data colellection. The research subjects were soccer athletes Gelora Fc Sintang U15 which consisted of 20 athletes. Based on the results of the study, it can be concluded that there isan influence of modification the rebounder tool toward the passing skills of the Gelora Sintang U15 soccer athletes. With the increase, the tcount value obtained is 4.98 and the ttable value on db (0.05 x 19) is 2.093. Therefore the value of t count is higher than t table (5.11> 2.093), this means that Ha is accepted, Ho is rejected, it can be concluded that there is an influence of modifying the rebounder toward the passing skills of football athletes PS Gelora U15 Sintang so that there is a 17.81% increase occur.Keywords: Football, passing, rebounder tool modification